CRIAÇÃO DE UMA UNIDADE DE DILUIÇÃO DE MEDICAMENTOS COM VISTA À QUALIFICAÇÃO DO PROCESSO DE TRABALHO EM SAÚDE E SEGURANÇA DO PACIENTE - Gomes, Carine Alves (2017)
The practice of prescribing, dispensing and diluting drugs in the hospital organization involves different professionals. For the nursing team it is the preparation and the administration that requires knowledge, attention and responsibility, mainly to avoid the error. The present study aimed to evaluate the possible contributions of the Drug Dilution Unit from the perspective of health professionals and managers. This is a qualitative and quantitative descriptive exploratory study, carried out from June to October 2016, in a medium-sized hospital, including a description of the process of implementation of the Drug Dilution Unit, the experiences, knowledge and needs for the creation of thistechnology. A sample of thirty professionals, composed of nursing technicians, nurses, pharmacists and managers, answered a self-administered questionnaire, structured with 12 closed questions (Likert-scale response) and 12 open questions about dilution unit technology in relation to quality and attention to the medication administration process, nursing care qualification and cost-effectiveness.The average score obtained in relation to patient safety was 14.8 points, reaching the percentage of 77.8% of the expected. The optimization in the medication assistance obtained 15.5 (81.8%), the qualification in the assistance, 14.7 (81.7%) and the cost-effectiveness, 15.8 (87.8%). In the perception of professionals, the unit promoted patient safety, benefited dilution standardization, adequate conference, asepsis of medications and effectiveness in the control, besides the organization and optimization of the time in the work processes, improvement in the qualification of the assistance of Nursing care in relation to patient care, reducing the number of adverse events and drug waste, resulting in a decrease in spending on drugs and materials. The implementation of the dilution unit had an impact on the hospital service with the disruption of the paradigms in relation to the medication assistance, since the change from routine preparation, dilution, to administration, underwent changes to obtain safety in the process. The new service was satisfactory as it stimulated the ability to rethink and seek innovations to transform work routines by qualifying care, medication and professional resources, providing greater patient safety. In view of the results, it can be concluded that the implementation of the Drug Dilution Unit favored the service for the offered advantages, of a technical, therapeutic, care and economic nature.This study allowed: favorable technical opinion of the Regional Nursing Council of Rio Grande do Sul (COREN-RS) and the 4th Regional Health Coordination of Santa Maria-RS; customization of computerized labels for drug identification; and, writing of dilution manual, standardized for the institution that allows to improve the routines of the unit.